Genetic Diversity of Imipenem-Resistant Acinetobacter baumannii Infections at an Intensive Care Unit - Amani Alnimr; Aisha Alamri; Afnan Alsultan (Critical Care Research and Practice)
Introduction. Imipenem-resistant Acinetobacter baumannii (IRAB) represents a major clinical threat. Dissemination in critical care areas necessitates effective action measures including genotyping tools to study the clonality of these strains and trace their origin. The main aim of this study is to assess the genetic relatedness between IRAB isolates in our institution intensive care units (ICU) which are at a particular risk of outbreaks. Methods. Nonreplicate IRAB strains were serially collected over 3 years period (January 2016–December 2018) from patients admitted to the ICU. The isolates were phenotypically identified by a matrix-assisted laser desorption/ionization time-of-flight- (MALDI-TOF-) based system (VITEK MS), and their susceptibility was tested by the phenotypic-based VITEK 2 system. Molecular fingerprinting was performed by enterobacterial repetitive intergenic consensus (ERIC-PCR) followed by hierarchal clustering. The patterns were analysed by the software of BioNumerics package version 7.6.3 (Applied Maths, Belgium). Results. A total of eighty IRAB were isolated from 31 colonization and 59 infection sites in patients admitted to the ICU. Sixty-two samples were respiratory in origin (77.5%). The generated dendrogram revealed distinct patterns for majority (95%) of the strains. Meropenem maintained activity against 43.8% of the imipenem-resistant A. baumannii. Conclusion. Meropenem can be a therapeutic option for imipenem-resistant A. baumannii. The banding patterns propose that multiple IRAB strains are circulating in the intensive care units of the institution. Drivers for this diversity need to be evaluated including antimicrobial consumption.